Ophiuroids from the Middle Triassic (Muschelkalk) of Sadowa Góra, Jaworzno (southern Poland) - Surmik, Dawid; Salamon, Mariusz A.; Chećko, Agnieszka; Kędroń, Karolina (Geology, Geophysics and Environment, 2020)
Ophiuroids belonging to Aspiduriella sp., Aspiduriella similis (Eck), and Arenorbis sp. are described from the Middle Triassic (Muschelkalk) strata of the Sadowa Góra Quarry (Jaworzno) in southern Poland. This is the only Polish location where three taxa of these ophiuroids have been found in one stratigraphic horizon (1st Wellenkalk). To date, only single taxa have been found in the Triassic sections of the eastern part of the Germanic Basin. Finally, other ophiuroid mass aggregations also known from Poland are presented.